INNOVATION AND COLLABORATION: STRATEGIES OF ONLINE FOOD DELIVERY MSMES AROUND STIE GANESHA TO ENHANCE COMPETITIVENESS IN THE DIGITAL ERA - Siregar, Fuad Gagarin; Noor, M. Arief; Saefullah, Aep (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the role of product innovation and strategic collaboration in enhancing the competitiveness of SMEs in the online food delivery business around STIE Ganesha. Using a qualitative approach, data were collected through in-depth interviews with 25 SME actors selected based on criteria such as minimal technology usage (e.g., WhatsApp Business) and experience collaborating with other SMEs. The findings reveal that menu innovation based on local trends, inter-SME collaboration for logistical efficiency (e.g., shared delivery fleets), and the use of simple technologies like WhatsApp broadcast lists significantly enhance business visibility and customer loyalty. Key challenges include limited access to technology training and reliance on third-party platforms, which impact profit margins. This study recommends developing a collaborative ecosystem involving academia, government, and business actors to strengthen SME capacity through locally tailored business incubation programs and technical mentoring